Improving the Quality of Protective Silicate Coatings of Metal Surfaces - A. Peristyi, Vladimir; I. Vesentsev, Alexander; F. Peristaya, Lidiya; M. Dang, Thuy; NKozyreva, Yuliya (International Journal of Engineering and Technology, 2018)
Reducing the chalking degree of protective and decorative silicate coatings of metal surfaces is achieved by increasing the free surface energy of the fillers by grinding them. The effect of surfactants on increasing the adhesive mechanical strength was confirmed.The increase in the dispersion of fillers (iron (III) oxide and chalk from 8â€“10 Âµm to 1â€“3 Âµm leads to a significant increase ( by 2 orders of magnitude) of chalking index of protective-decorative silicate coatings for metal surfaces. It is shown that the introduction of a high content of latex and liquid glass into the formulation reduces the chalking index only 2 times. The effect of anionic surfactants of polyethylene glycol sulfoethoxylates on the increase in wetting and adhesion effects, which is the result of the increased mechanical strength of fireproof and environmentally friendly coatings, was confirmed.Â Â Â